2021
DOI: 10.1038/s41594-021-00590-w
|View full text |Cite|
|
Sign up to set email alerts
|

Retinoic acid signaling is critical during the totipotency window in early mammalian development

Abstract: Totipotent cells hold enormous potential for regenerative medicine. Thus, the development of cellular models recapitulating totipotent-like features is of paramount importance. Cells resembling the totipotent cells of early embryos arise spontaneously in mouse embryonic stem (ES) cell cultures. Such ‘2-cell-like-cells’ (2CLCs) recapitulate 2-cell-stage features and display expanded cell potential. Here, we used 2CLCs to perform a small-molecule screen to identify new pathways regulating the 2-cell-stage progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 68 publications
1
45
0
Order By: Relevance
“…ZFP281 and RAR binding motifs were found only in C3H-specific DEGs ( Figures 4 F and S4 A). RAR has been shown to affect transcriptional reprogramming, possibly through opening of inaccessible sites in somatic chromatin such as Pou5f1 and Utf1 loci ( Miyamoto et al., 2018 ), and RA activity in early embryos is required for embryonic gene activation ( Iturbide et al., 2021 ). ZFP281, a zinc finger TF, maintains the pluripotency network in ES cells through the direct activation of Nanog and other pluripotency-related genes by binding to promoters with OCT4 and SOX2 ( Kim et al., 2008 ; Wang et al., 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…ZFP281 and RAR binding motifs were found only in C3H-specific DEGs ( Figures 4 F and S4 A). RAR has been shown to affect transcriptional reprogramming, possibly through opening of inaccessible sites in somatic chromatin such as Pou5f1 and Utf1 loci ( Miyamoto et al., 2018 ), and RA activity in early embryos is required for embryonic gene activation ( Iturbide et al., 2021 ). ZFP281, a zinc finger TF, maintains the pluripotency network in ES cells through the direct activation of Nanog and other pluripotency-related genes by binding to promoters with OCT4 and SOX2 ( Kim et al., 2008 ; Wang et al., 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, cluster 3 showed higher retinoid X receptors alpha (Rxra) gene expression (log 2 (FoldChange) = 1.41) (Figure 7A), which is a critical receptor that controls retinoic acid activation. Recent studies have showed that Rxra expression is upregulated in 2CLCs, and the high expression of retinoic acid can reprogram mESCs to the 2CLC state [28,29]. In the predicted pathway regulation analyses by the IPA, several low expression genes in cluster 3 revealed differentiation-related genes including Fgf2 and Vegfa, where both are differentiation factors of ESCs [16,30].…”
Section: Discussionmentioning
confidence: 98%
“…Taken together with these observations, our study demonstrates that BMP4 signaling plays an essential role in establishing the Totipotent state. A recent study found that retinoic acid can also induce a 2C-like Totipotent state in ESCs ( 27 ). Although retinoic acid is not used to culture mouse ESCs as it induces their differentiation towards neuroectoderm lineage ( 28 ), it may act in conjunction with BMP4 signaling to induce the Totipotent state.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor Gata2 induces the Totipotent state by inducing MERVL expression (19). The Totipotent state can also be enhanced in cultured ESCs in various ways: over-expression of Duxf3 and Nelfa genes and miR-344 microRNA; altering chromatin states through knockout of Lsd1 and Hdac inhibitors; altering metabolic states through sodium acetate and α-ketoglutarate; treating with a combination of small-molecule inhibitors and retinoic acid (21)(22)(23)(24)(25)(26)(27). Pluripotent cells are marked by the expression of Oct4, Sox2, Klf4, Nanog, Rex1 and other transcription factors known to form a selfreinforcing gene regulatory network (28,29).…”
Section: Introductionmentioning
confidence: 99%